Employment Opportunities And Human Resources Development In Digital Era: A Case Study In Industrial Sector - Devi Asiati; Gutomo Bayu Aji; Vanda Ningrum; Ngadi Ngadi; Triyono Triyono; Fuat Edi Kurniawan; Norman Luther Aruan; Yanti Astrelina Purba (Journal of Indonesian Social Sciences and Humanities, 2018)
Transformation of digitalization in large industries has an impact on the automation of production equipment, including the replacement of production machines from conventional machines (manual) to digital machines. Meanwhile, automation of production equipment requires workers with higher skills, in fact the existing workforce does not have expertise in carrying out all-digital equipment. The impact is a reduction in labor (layoffs). Machine replacement is done in stages so that the reduction of workforce (PHK) in bulk is not visible. However, the inconsistency between the preparation in the world of education and the needs in the world of work continues to occur today. Until now, vocational development based on local resources has not been operating optimally and needs serious attention from the local government. The government on various occasions mentioned four leading sectors that will be strengthened in the development of vocational institutions, namely maritime, tourism, agriculture (food security), and the creative industry. In addition, the government is also developing a policy scheme for Skill Development Funds (SDF), which is a skills improvement program for workers affected by automation (PHK), including through Vocational Training Center (BLK).